Morphological evaluation of compatibility of ventricular myocardium and external restrictive elastic sac of the original construction made from titanium nickelide after its implantation during the experiment - V. A. Kazakov; A. A. Lezhnev; V. M. Shipulin; Ye. V. Krivoschyokov; I. V. Sukhodolo (Бюллетень сибирской медицины)
The objective of this study is a morphological evaluation of compatibility of ventricular myocardium with the device of our original construction for restriction of heart chambers dilatation. In the experiment the device made from titanium nickelide was implanted into 8 outbred dogs with the previously induced experimental model of left ventricular aneurism. The animals were excluded from the experiment in 1, 3 and 6 months after implantation of an external restrictive elastic sac. Histological preparations of myocardium samples, which were in an immediate contact with titanium nickelide fibers were the subjects for studying of general tissue response to the presence of an implanted device. No data evidencing negative effect of an external restrictive elastic titanium nickelide sac on ventricular myocardium have been found. It means that an implanted sac has a satisfactory compatibility with biological tissues just as like as any other implant made from titanium nickelide.